46 PERCENTAGE PREDICTED MAXIMUM HEART RATE IN CORONARY ARTERY DISEASE BY STRESS TESTING IN A COMMUNITY HOSPITAL. (10th December 2015) - Mankan, N.; Madhunapantula, S.; Banuru, S.; Islam, S.
Abstract : Purpose of Study: Multiple studies have suggested sensitivity and specificity of 65% and 85% for exercise stress tests and 89% and 65% for pharmacological stress testing. Our study was to evaluate for a correlation between the stress testing, percentage predicted maximum heart rate (PPMHR) and coronary anatomy. Method: This was a retrospective study involving all the hospital patients who had a stress test correlated with their ECGs during the period of May 2002 to May 2003. By angio-catheterizations, all stenoses > 70% were considered as significant for all the vessels except for the left main artery for which > 50% was considered significant. We also divided them into subgroups based on PPMHR as < 50, 50-85 and > 85. Thallium (Th) was used at rest and sestamibi (Tc99) was used during the stress component of the study. As per ACC/AHA classification: A = 1-vessel, no left anterior descending (LAD); B = 1-vessel, non-proximal LAD; C = 1-vessel, proximal LAD; D = 2-vessel, no LAD; E = 2-vessel, non-proximal LAD; F = 2-vessel proximal LAD; G = 3-vessel, non-proximal LAD; H = 3-vessel, proximal LAD. Results: We found 39 abnormal stress studies (19 had pharmacological [Dipyridamole] stress test and 20 had exercise induced) of which 34 were true positives, 2 inconclusive and 3 false positive. Of the 39 cases, PPMHR varied from 38-137. Metabolic equivalents (METS) achieved during exercise stress test varied from 4-14. As per ACC/AHC coronary anatomy classification, we found 7 patients with 0 vessel disease (VD); 5 patients with 1 VD (A + B + C); 11 patients with 2 VD (D + E + F) and 12 patients with 3 VD (G + H). Among the patients with PPMHR < 50, there were 6 patients (0 VD-1, 1 VD-2, 2 VD-2, 3 VD-1); with PPMHR 51-85 there were 17 patients (0 VD-3, 1 VD-1, 2 VD-5, 3 VD-8); and with > 85 PPMHR there were 12 patients (0 VD-2, 1 VD-2, 2 VD-5, 3 VD-3) and for 4 patients PPMHR was not available. Among those who underwent dipyridamole test, PPMHR < 50 was seen in 6 patients (0 VD-1, 1 VD-2, 2 VD-2, 3 VD-1); between 50-85 9 patients (0 VD-2, 1 VD-0, 2 VD-3, 3 VD-4); > 85 0 patients and for 4 patients PPMHR was unavailable. Those 20 patients who had an exercise stress test, PPMHR 50 had 0 patients; 51-85 had 8 patients (0 VD-1, 1 VD-1, 2 VD-2, 3 VD-4); and > 85 had 12 patients (0 VD-2, 1 VD-2, 2 VD-5, 3 VD-3). Conclusion: In pharmacological and exercise stress testing PPMHR is an effective non-invasive and reliable test for the diagnosis of CAD. Exercise stress testing achieves higher PPMHR than pharmacological testing. Higher sensitivity/specificity was observed with higher PPMHRs.